Green and facile approach to prepare polypropylene/in situ reduced graphene oxide nanocomposites with excellent electromagnetic interference shielding properties. Issue 53 (28th August 2018) - George, Gejo; Simon, Sanu Mathew; V. P., Prakashan; M. S., Sajna; Faisal, Muhammad; Wilson, Runcy; Chandran, Anoop; P. R., Biju; Joseph, Cyriac; Unnikrishnan, N. V.
Abstract : Fabrication of PP/ in situ reduced GO nanocomposites with excellent EMI shielding capability realized via a facile and green route. Abstract : The present work discloses the admirable electromagnetic interference shielding effectiveness (∼50 dB at X and Ku Bands) realized by means of excellent dispersion state of reduced graphene oxide (rGO) in a polypropylene (PP) matrix, even at high concentrations (20 wt%). This was achieved by means of a latex method (polymer matrix; here PP in the aqueous emulsion state) combined with in situ reduction of graphene oxide usingl -ascorbic acid as the reducing agent (green approach). A probable reaction mechanism between the maleic acid anhydride part of the PP matrix with the remaining –OH groups of rGO which may further assist in the better dispersion of graphene is also suggested. The prepared PP/rGO nanocomposites showed a percolation threshold in between that of 1.5 and 3 wt% rGO content. The microcapacitor and the conductive pathway formation in the system are explained nicely with the help of a schematic diagram. The electromagnetic interference shielding effectiveness (EMI SE) of 50 and 48 dB achieved for the X and Ku-bands for the 20 wt% rGO filled sample is one of the best among current works based on GO as the filler. The thermal stability of the samples increased marginally due to the addition of thermally stable rGO. The crystallization temperature increased with increasing rGO content owing to its good nucleating ability, whereas the melting characteristics shifted from double to single melting behavior possibly due to the ability of rGO to explicitly nucleate a particular polymorph of PP. A simple, cost efficient, green and promising approach to prepare non-polar polymer/graphene nanocomposites with a good dispersion state of graphene and excellent properties is reported in the present work.